Wideband nonlinear dynamic vibration absorber using piecewise linear stiffness for effective structural vibration suppression - Mustaffer, Muhammad Harith (2020)
Vibration has become a major concern nowadays due to its tendency o produce undesirable noise and to potentially result in a harmful response. Generally, there are two ways to control the level of vibration in machines or structures. One of the techniques is by isolating the receiver of the vibration from the source. Isolation is a feasible solution if the level of vibration of the source cannot be altered. In some cases, the source of the vibration must be suppressed, hence isolation may not be a feasible solution, For these cases, the dynamic vibration absorber (DVA) is normally used. This is done by attaching another single-degree-of-freedom (SDOF) oscillating system onto the vibrating primary structure. The DVA is designed 10 have a natural frequency similar to the troublesome frequency of the primary structure. Many of the currently available passive dynamic vibration absorbers are not fully efficient in suppressing the vibration of the primary structure due to narrow operating frequency bandwidth. The performance of the DVA deteriorates even more in the application where the structure’s troublesome frequency varies over time and it requires constant retuning of its natural frequency. Iis low tolerance towards frequency mistuning increase the level of vibration. Thus. it is necessary to design a DVA with efficient tuning capability and less sensitive towards mistune. In this study, the nonlinear dynamic vibration absorber (NDVA) with a tuncable piccewise linear stiffness mechanism which behaves similar to hardening stiffess mechanism was designed. The hardening stiffiess is proven to perform better due to the larger suppression bandwidth. However, unlike the hardening stiffness mechanism, the proposed piecewise linear siffness mechanism offers better tuning capability. The mechanism is composed of a cantilever beam constrained by two limit blocks which are adjustable in both horizontal and vertical directions. Firstly, the analytical study was performed before developing the NDVA to study its static and dynamic characteristics. The characterization study of the NDVA includes different limit block configurations (horizontal position and vertical gap). input amplitude, mass, and stiffiess. Once the NDVA fabricated, the analytical results were then validated experimentally by conducting static and dynamic measurements. The quasi-static measurement was done by exciting, the base of the NDVA at low frequency to measure for force-deflection relationship. As for dynamic measurement, the base of the NDVA was once again excited on the electrodynamic shaker using sweep-up and sweep down of the excitation frequency between 10 Hz to 40 Hz. Finally, the performance of the NDVA in suppressing the vibration of the primary. structure was measured and compared with its equivalent linear DVA. This was done by attaching the NDVA on the structure connected to the shaker and was excited using a similar range of sweep-up and sweep down excitation frequency. The results show a promising performance of the NDVA with an increase in suppression frequency bandwidth compared 10 its equivalent linear DVA.